The Expert Validation of a Guided Inquiry-Based WordPress Student Worksheet Integrated with Islamic Values on the Circulatory System - Susilawati; Umar Faruq; Annisa Fazila Sabrina Damanik; Adisti Yuliastrin (ISEJ : Indonesian Science Education Journal, 2026)
This study aimed to develop and validate a guided inquiry-based student worksheet (LKPD) supported by WordPress and integrated with Islamic values for the circulatory system. The study used Research and Development with the Plomp model. This manuscript reports the expert-review stage of the prototyping phase. Three validators were selected purposively: one expert in teaching-material design, one expert in science/biology content, and one expert in Qur'anic exegesis and Hadith. Validation used domain-specific instruments consisting of 30, 26, and 17 items, respectively. Each item was rated on a four-point scale, analyzed as a percentage of the maximum score, and supplemented with qualitative comments for product revision. The teaching-material, subject-matter, and Islamic-values validation scores were 95.0%, 90.0%, and 92.5%, respectively, producing an overall mean of 92.5% in the very valid category. The lowest sub-aspect was the integration of Islamic values within the subject-matter instrument (75.0%), which prompted revisions to connect religious sources, scientific explanations, and reflection activities more coherently. The results indicate that the revised LKPD is sufficiently valid to proceed to practicality and effectiveness testing. The main limitation is that each domain was assessed by one expert; therefore, inter-rater agreement and learning outcomes were not examined.